English Learning by Using Joyful Learning for Early Children at PIAUD Ummul Habibah in Klambir 5 Kebon - Sari, Indah; Utami, Rahayu Dwi; Widya, Rika; Nuraisyah , Julia; Fanny, Adinda Dwi (Proceeding International Conference on Malay Identity, 2024)
This study aimed to analyse the application of joyful English learning methods for early childhood at PIAUD Ummul Habibah, Klambir 5 Kebon. Using the joyful learning approach, this study examined how a fun learning atmosphere could increase students' motivation and engagement in the English learning process. The technique of data collection by conducting the interview. The subjects of this study were three teachers at PIAUD Ummul Habibah Klambir 5 Kebon.The results showed the teachers implemented the joyful learning in the class based on the daily plan of English learning. Moreover, they also that used of various creative activities, such as games, songs and stories, successfully attracted children's interest and accelerated their understanding of English. In addition, the positive and interactive environment also contributed to the children's social and emotional development. This study recommends the integration of joyful learning methods in the English curriculum to support effective and fun learning for early childhood.